2022
DOI: 10.1186/s12951-022-01538-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial metal nanoclusters

Abstract: Combating bacterial infections is one of the most important applications of nanomedicine. In the past two decades, significant efforts have been committed to tune physicochemical properties of nanomaterials for the development of various novel nanoantibiotics. Among which, metal nanoclusters (NCs) with well-defined ultrasmall size and adjustable surface chemistry are emerging as the next-generation high performance nanoantibiotics. Metal NCs can penetrate bacterial cell envelope more easily than conventional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 120 publications
(157 reference statements)
0
12
0
Order By: Relevance
“…The antimicrobial mechanisms of ultrasmall metal NCs can be divided according to the following aspects (Figure 6): cell wall and cell membrane disruption, metal ion release, toxic reactive oxygen species (ROS) production, intracellular component disturbance, antimicrobial agent delivery, and photoactivation mechanisms. [19] Wang et al synthesized high-purity Au25 NCs and found that their killing effect on Gram-negative bacteria (Escherichia coli) was significantly better than that against Gram-positive bacteria (Staphylococcus aureus [S. aureus]) (Figure 7) at certain concentrations and after treatment for different lengths of time. After further investigation of their antibacterial mechanism, it was determined that bacterial cell death was mainly due to the synergistic effects of membrane and DNA damage, oxidative stress, and energy metabolism alterations, showing the potential of these NCs as a nanoantibiotic.…”
Section: Antimicrobial Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The antimicrobial mechanisms of ultrasmall metal NCs can be divided according to the following aspects (Figure 6): cell wall and cell membrane disruption, metal ion release, toxic reactive oxygen species (ROS) production, intracellular component disturbance, antimicrobial agent delivery, and photoactivation mechanisms. [19] Wang et al synthesized high-purity Au25 NCs and found that their killing effect on Gram-negative bacteria (Escherichia coli) was significantly better than that against Gram-positive bacteria (Staphylococcus aureus [S. aureus]) (Figure 7) at certain concentrations and after treatment for different lengths of time. After further investigation of their antibacterial mechanism, it was determined that bacterial cell death was mainly due to the synergistic effects of membrane and DNA damage, oxidative stress, and energy metabolism alterations, showing the potential of these NCs as a nanoantibiotic.…”
Section: Antimicrobial Applicationsmentioning
confidence: 99%
“…[60] In addition to Au NCs, Ag NCs, Cu NCs, alloy NCs, and related composite nanostructures also have antimicrobial applications, which are related to their basic composition and individual properties. [19] Zheng et al established a library of full-spectrum water-soluble AuxAg25MHAx(-)18NCs. When the alloy composition was extended to the full spectral range, showing U-shaped antimicrobial behavior, the alloy nanomaterials usually exhibited better performance in applications, indicating that alloy nanomaterials have unexpected complexity and deserve further investigation by multidisciplinary groups.…”
Section: Antimicrobial Applicationsmentioning
confidence: 99%
See 3 more Smart Citations